Using Caffeine as a Water Quality Indicator in the Ambient Monitoring Program for Third Fork Creek Watershed, Durham, North Carolina - Porché L. Spence (SAGE Publishing, 2015)
Caffeine has been suggested as a chemical indicator for domestic wastewater in freshwater systems, although it is not included in water quality monitoring programs. The Third Fork Creek watershed in Durham, NC, is highly urbanized, with a history of receiving untreated wastewater from leaking and overflowing sanitary sewers. The poor water quality originating in the Third Fork Creek watershed threatens its intended uses and jeopardizes drinking water, aquatic life, and recreational activities provided by Jordan Lake. Organic waste contaminants have been detected in both Third Fork Creek watershed and Jordan Lake; however, the sampling periods were temporary, resulting in a few samples collected during nonstorm periods. It is recommended that (1) the concentration of caffeine and other organic waste contaminants are determined during storm and nonstorm periods and (2) caffeine is monitored regularly with traditional water quality indicators to evaluate the health of Third Fork Creek watershed.